ミズホ コウゲン ニ オケル テイジョウテキ ナ カタバティック フウ ノ カンソク - 小林, 俊一; コバヤシ, シュンイチ; 横山, 宏太郎; ヨコヤマ, コウタロウ; KOBAYASHI, Shun'ichi; YOKOYAMA, Kotaro (国立極地研究所, 1976)
P(論文) 第14次南極地域観測隊における研究観測の気象部門は,内陸調査旅行中みずほ高原で,ラジオゾンデとパイロットバルーンによりカタバティック風の垂直構造について調べた.観測した回数は充分多くはなかったが,みずほ高原におけるカタバティック風の厚さは接地逆転層に一致していることが結論された.逆転層の厚さは夏(250m)より冬(600m)厚く,逆転層の強さ(温度差ΔT)は,夏(ΔT≈5℃)より冬(ΔT≈15～20℃)強かった. This paper describes the study on the thickness and intensities of surface inversions and vertical wind profiles in a katabatic wind layer existing semipermanently in the Mizuho Plateau. Observations of vertical temperature and wind profiles in lower layer were carried out ten times by means of radio sondes, and five times by pilot balloons to know upper wind directions, at mainly Mizuho Camp (70°42.6'S, 44°18.9'E, 2,200 m) in 1973. From results obtained, it was found that the thickness of the surface inversion layer were about 600 m in winter and 250 m in summer, and temperature difference between the top and the bottom of the surface inversion layer (intensity) were in the range from 15 to 20℃ in winter and about 5℃ in summer. departmental bulletin paper